Effects of basic medical insurance integration on subjective wellbeing of residents in China: empirical evidence from a quasi-experiment - Xin Na; Lingzhi Ding; Junxia Wang; Shuzhen Chu (Frontiers Media S.A., 2023)
IntroductionEnhancing the wellbeing of residents through universal health coverage (UHC) is a long-term policy goal for China. In 2016, China integrated the New Rural Cooperative Medical Scheme (NRCMS) and the Urban Resident Basic Medical Insurance (URBMI) into the Urban and Rural Resident Basic Medical Insurance (URRBMI) to address the problem of fragmentation.ObjectiveThe objective of this study was to investigate whether the integration of basic medical insurance had an impact on the subjective wellbeing of Chinese residents.MethodsUsing the China Household Finance Survey data of 2015 and 2019, we empirically estimated the influence of the integration of basic medical insurance on Chinese residents through the difference-in-difference method based on propensity score matching (PSM-DID).ResultsOur findings indicate that the integration of basic medical insurance improved the subjective wellbeing of the insured population. Additionally, through heterogeneity testing, we validated that the integration increased the subjective wellbeing of residents from less developed regions in West China and rural areas, as well as those with older adult dependents. However, the subjective wellbeing of low-income groups, who were expected to benefit more from the URRBMI, did not improve significantly, at least in the short term.ConclusionAccording to our research, the integration of basic medical insurance in China supports the country's objective of achieving equality and providing universal benefits for its residents. The introduction of the URRBMI has had a positive impact on the subjective wellbeing of insured individuals. This is particularly beneficial for disadvantaged groups in less developed regions, as well as for residents with older adult dependents. However, the subjective wellbeing of the middle-income group has improved significantly, whereas that of the low-income group, despite being the intended beneficiaries of the integration, did not show significant improvement.RecommendationsFrom a funding perspective, we recommend establishing a dynamic adjustment funding system that links residents' medical insurance funding standards with their disposable income. Regarding the utilization of the URRBMI, the benefit packages should be expanded, particularly by covering more outpatient services through risk pooling. We call for further research with additional data and continued efforts on improving wellbeing of residents, particularly for disadvantaged populations.